PENGARUH METODE DEMONSTRASI BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR SISWA IPA KELAS V SDN JURUMUDI 4 KOTA TANGERANG - Febriyanti Rizki Nurfadilah; Harlinda Syofyan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
It study is motivated by the low of learning outcomes of fifth grade students in natural science subject. The objective of this research is to determine the impact of the demonstration method supported by audio-visual media on the learning outcomes of fifth grade students at SDN Jurumudi 4 Tangerang City. This study uses an experimental method with a research design which will be used is a pre-experimental design (non-design), namely one group pretest-posttest design. It research used pretest before treatment and posttest after treatment. The population of this study were 48 students of class V. The Cluster Random Samplingis was technique that used as sampling. The sample used was 25 students from class V B. The data collection technique used was a test in the form of multiple choice questions and non-test in the form of an observation sheet/cheak list. It research instrument was a multiple choice test consisting of 20 questions. The results displayed that the average score for the pretest learning outcomes was 70.60 and the average score for the posttest learning outcomes was 83.60, for the significance value for the pretest learning outcomes data was 0.076 and the significance for the posttest learning outcomes data was 0.099 respectively -each significance value is more than 0.05. These results state that there are differences in posttest learning outcomes that are greater than pretest learning outcomes. Submission of the hypothesis with the T-test obtained a significance value of 0.000<0.05, that means that there is a significant difference, however the value of tcount = 9.390> ttable = 2.069, so the results obtained show that H0 is rejected and H1 is accepted, which means there is an influence of application demonstration method assisted by audio-visual media on students' science learning outcomes.